APOBEC3D and APOBEC3F Potently Promote HIV-1 Diversification and Evolution in Humanized Mouse Model - Sato, Kei (Public Library of Science, 2014)
Several APOBEC3 proteins, particularly APOBEC3D, APOBEC3F, and APOBEC3G, induce G-to-A hypermutations in HIV-1 genome, and abrogate viral replication in experimental systems, but their relative contributions to controlling viral replication and viral genetic variation in vivo have not been elucidated. On the other hand, an HIV-1-encoded protein, Vif, can degrade these APOBEC3 proteins via a ubiquitin/proteasome pathway. Although APOBEC3 proteins have been widely considered as potent restriction factors against HIV-1, it remains unclear which endogenous APOBEC3 protein(s) affect HIV-1 propagation in vivo. Here we use a humanized mouse model and HIV-1 with mutations in Vif motifs that are responsible for specific APOBEC3 interactions, DRMR/AAAA (4A) or YRHHY/AAAAA (5A), and demonstrate that endogenous APOBEC3D/F and APOBEC3G exert strong anti-HIV-1 activity in vivo. We also show that the growth kinetics of 4A HIV-1 negatively correlated with the expression level of APOBEC3F. Moreover, single genome sequencing analyses of viral RNA in plasma of infected mice reveal that 4A HIV-1 is specifically and significantly diversified. Furthermore, a mutated virus that is capable of using both CCR5 and CXCR4 as entry coreceptor is specifically detected in 4A HIV-1-infected mice. Taken together, our results demonstrate that APOBEC3D/F and APOBEC3G fundamentally work as restriction factors against HIV-1 in vivo, but at the same time, that APOBEC3D and APOBEC3F are capable of promoting viral diversification and evolution in vivo.